2010
DOI: 10.3109/00048670903489866
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Prevalence of Mental Health Problems in Deaf and Hearing Children and Adolescents in Australia

Abstract: The known heterogeneity within the Australian deaf child and adolescent population with respect to preferred mode of communication has important implications not only for the appropriate selection and use of psychiatric instruments in assessing child and adolescent mental health but also for the accurate reporting of the prevalence and nature of mental health problems within this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
26
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 19 publications
4
26
0
Order By: Relevance
“…10,26,34,41 Two studies included community-based samples and found that parentreported levels of anxiety were higher in HI than in NH participants, 34 whereas self-reported levels of anxiety were equal in both groups. 26 For children with profound losses and/or attending special schools, the 2 available studies both revealed more self-reported anxiety in HI compared with NH children. 10,41 So, HI individuals have at least as much anxiety as NH individuals, but it is plausible that they in fact experience more anxiety, especially the children with profound losses attending special schools.…”
Section: Internalizing Symptomsmentioning
confidence: 99%
See 1 more Smart Citation
“…10,26,34,41 Two studies included community-based samples and found that parentreported levels of anxiety were higher in HI than in NH participants, 34 whereas self-reported levels of anxiety were equal in both groups. 26 For children with profound losses and/or attending special schools, the 2 available studies both revealed more self-reported anxiety in HI compared with NH children. 10,41 So, HI individuals have at least as much anxiety as NH individuals, but it is plausible that they in fact experience more anxiety, especially the children with profound losses attending special schools.…”
Section: Internalizing Symptomsmentioning
confidence: 99%
“…For somatization, 6 different studies were carried out. [4][5][6]20,26,32 Some researchers found no difference in level of somatization between HI and NH children and adolescents, 5,26,32 while others reported more somatic complaints in HI individuals, 4,6,20 with a reported prevalence varying from 17% to 20% for HI participants. 4,6 These seemingly inconsistent outcomes could not be explained by differences in study samples, since community-based samples as well as samples derived from special schools were included in both groups.…”
Section: Internalizing Symptomsmentioning
confidence: 99%
“…On the other hand, according to some of these studies, aggression levels of these children are close to their peers with no hearing-impairment and other problems experienced are not caused by hearing impairment (Konuk, 2006;Remine & Brown, 2010). According to the results of several studies, many problems including aggressive behaviors are reduced with the development of social skills, problem solving and communication skills (Pakaslahti et al, 1996;Chang & Sanna, 2003;Fung & Tsang, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…These individuals may also display difficulties in abstract thinking and problem-solving skills [7], ability to form peer relationships, low self-esteem [8] and ultimately increased psychological distress [9]. Due to the aforementioned, individuals with hearing loss are at risks of health and environmental hazards, more susceptible to social maladjustment, poor quality of sleep and likelihood of internalizing depressive symptoms when compared to hearing peers [10].…”
Section: Introductionmentioning
confidence: 99%